A simulation model of array tunable QCL and its verification in liquid sample sensing (edible oil) - Song, Weifan (Nanyang Technological University, 2022)
In this paper, a scheme using Quantum Cascade Laser (QCL) arrays as the light source to conduct the sensing of the edible oil is presented, where the simulated QCL array covers the spectrum of 798cm-1 to 3200cm-1. To verify the design’s practicability, a parallel verification experiment using the Fourier Transformation Infrared (FTIR) Sensing is conducted to provide the benchmark of the simulated design. The parallel experiment and the simulated experiments comparison show the possible construction of a more compact system using the QCLs while yielding similar accuracy as the FTIR counterpart and the possible robustness of the QCL system related to certain samples.